From Ritual to Solidarity: The Role of Pattaungeng Tradition in Social Cohesion of the Community - A. Octamaya Tenri Awaru (Indonesian Journal of Religion and Society, 2025)
The Pattaungeng tradition is one of the cultural heritages of the Bugis people in Soppeng Regency, which is held annually as a form of gratitude for the harvest and respect for ancestors. This research aims to examine the role of the Pattaungeng tradition in strengthening social cohesion within the community. The method used is descriptive qualitative research with data collection techniques including observation, interviews, and documentation. The research informants include traditional figures, village government officials, and community members who actively participate in the tradition. The research findings indicate that the Pattaungeng tradition plays a significant role in strengthening social cohesion thru five main dimensions: (1) preserving cultural identity as a collective symbol of Bugis society, (2) intergenerational integration thru the transfer of values and norms, (3) the practice of collective deliberation (tudang sipulung) as a means of building consensus, (4) symbolic relationships with religion that provide spiritual legitimacy for cultural practices, and (5) strengthening socio-economic networks thru community cooperation and mutual contribution. This finding confirms that Pattaungeng is not merely a cultural ritual, but also a social mechanism that maintains solidarity, prevents individualism, and strengthens community bonds amidst the currents of modernization.